DIRECTIONS OF INNOVATIVE DEVELOPMENT OF THE HOTEL BUSINESS - Скриннік, Вікторія; Калашник, Олена; Мороз, Світлана (SWorldJournal, 2025)
The article examines the essence and classification of innovations in the hotel business as a key factor in increasing the competitiveness of hospitality enterprises. The main types of innovations are identified. Modern trends in the development of innova